2010
DOI: 10.1007/s00253-010-2934-3
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial laccase from marine microbial metagenome exhibiting chloride tolerance and dye decolorization ability

Abstract: Laccases are blue multicopper oxidases with potential applications in environmental and industrial biotechnology. In this study, a new bacterial laccase gene of 1.32 kb was obtained from a marine microbial metagenome of the South China Sea by using a sequence screening strategy. The protein (named as Lac15) of 439 amino acids encoded by the gene contains three conserved Cu(2+)-binding domains, but shares less than 40% of sequence identities with all of the bacterial multicopper oxidases characterized. Lac15, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 34 publications
3
76
0
1
Order By: Relevance
“…The first structure of a bacterial laccase was of that from Bacillus subtilis, named CotA laccase (Enguita et al 2003). The most recent report of a bacterial laccase is from a marine microbial metagenome, which also exhibits dye decolorization ability (Fang et al 2011). Because of the extreme thermostability and pH stability of prokaryotic enzymes compared to eukaryotic enzymes, bacterial laccases may be ideal for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The first structure of a bacterial laccase was of that from Bacillus subtilis, named CotA laccase (Enguita et al 2003). The most recent report of a bacterial laccase is from a marine microbial metagenome, which also exhibits dye decolorization ability (Fang et al 2011). Because of the extreme thermostability and pH stability of prokaryotic enzymes compared to eukaryotic enzymes, bacterial laccases may be ideal for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that bacterial laccases showed superior tolerance to various harsh environments. Fang et al (2011) isolated a bacterial laccase from a marine microbial metagenome that exhibited chloride tolerance and dye decolorization ability. The spore laccase of Bacillus licheniformis LS04 was found to be quite stable at high temperatures, showed no loss of laccase activity after 10 days of incubation at pH 9.0, and demonstrated organic solvent tolerance (Lu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sequenced-based screening has been used together with NGS technologies in the identification of PKS and NRPS clusters from a number of cultured strains [177]. Further to this, sequence-based analysis of marine metagenomic libraries has to date revealed the presence of a number of enzymes including peptidases [178], alkane hydroxylases [179], laccase [15], and a fumarase [17]. In the case of the peptidases, the Sargasso Sea Whole Genome Sequence (WGS) dataset, involving a total of 1.045 billion base pairs of metagenomic DNA sequence, with over 1.2 million protein encoding ORFs [180], was analyzed by Cotrell and coworkers [178] by using BLAST, in the identification of potential hydrolases.…”
Section: Strategies For Marine Natural Compounds Discovery From Mamentioning
confidence: 99%